Norovirus infections in young children in Lusaka Province, Zambia: clinical characteristics and molecular epidemiology. Issue 1 (December 2017) - Howard, Leigh; Mwape, Innocent; Siwingwa, Mpanji; Simuyandi, Michelo; Guffey, M.; Stringer, Jeffrey; Chi, Benjamin; Edwards, Kathryn; Chilengi, Roma
Abstract Background The burden, clinical features, and molecular epidemiology of norovirus infection in young children in southern Africa are not well defined. Methods Using data from a health facility-based surveillance study of children <5 years in Lusaka Province, Zambia presenting with diarrhea, we assessed the burden of norovirus infection. A convenience sample of 454 stool specimens was tested for norovirus using reverse-transcriptase polymerase chain reaction (RT-PCR). RT-PCR positive samples underwent additional nucleotide sequencing for genogroup and genotype identification. Clinical features and severity of diarrheal illnesses were compared between norovirus-positive and -negative subjects using Chi-squared and t-tests. Results Norovirus was detected in 52/454 (11.5%) specimens tested. Abdominal pain, fever, and vomiting were the most common presenting features in norovirus-associated illnesses. However, there were no significant differences in the clinical features of norovirus-positive compared to norovirus-negative illnesses. Of 43 isolates that were available for sequencing, 31 (72.1%) were genogroup II (GII) and 12 (27.9%) were genogroup I (GI). The distribution of genotypes was diverse. Conclusions Noroviruses were detected in approximately 10% of young children with diarrhea in the Lusaka Province of Zambia, with GII representing the majority of infections. These findings support the role of norovirus in symptomatic diarrhea disease in Africa. Further studies are needed to confirm these observations and to evaluate prevention strategies.